An Examination of Brentano’s Intentionality and Moore’s Sense-Data Conception of Reality - Isenyo Solomon Ogaba (dialektika kontemporer, 2021)
It’s not very easy to assert or claim that our knowledgeof reality is direct or indirect,so,it becomes difficult to establish that which constitutes our objects of knowledge. Equally, the fact that, it has not been objectively proven that the human mind has a precise location in or outside the body, doesnotinvalidate the existence of the human mind. As such, this paper attempts at exposing the nature, character and objects of the mind in process of cognition by critically analyzing the distinction between Brentano’s conception of intentionality which exposes the character of the mind to be about something (aboutness) and possible mental objects of thought and Moore’s sense-data conception of reality which exposes the process by which cognition(perception) takes place. Consequently, the research uncovered that, the meta-epistemological outlookofboth Brentano and Moore are more convergent than divergent because they hold strongly to the analytical, phenomenological and rationalistic approaches to knowledge formation .The paper,however, concludes that Moore was basically concerned with how the physical world and things in it appears or are given to us via theprocess of mind’s cognition, while Brentano was concerned with what constitutes objects of the mental (mind).